Treatment completion and safety profile of once-weekly 3HP regimen for tuberculosis preventive treatment in children and adolescents: a systematic review - Sipang Pangprasertkul; Nida Buawangpong; Kanokporn Pinyopornpanish; Wichuda Jiraporncharoen; Chaisiri Angkurawaranon (BMC Infectious Diseases)
Abstract Background Children and adolescents are at increased risk of progressing from latent to active tuberculosis (TB). The 3-month, once-weekly isoniazid and rifapentine (3HP) regimen offers a shorter tuberculosis preventive treatment (TPT) option. However, evidence regarding its completion rates and safety in these populations remains limited. Objective To evaluate treatment completion rates and adverse events associated with the 3HP regimen in children and adolescents. Methods A systematic review of studies evaluated the 3HP regimen in children and adolescents with LTBI was conducted. Databases including PubMed, Embase, Cochrane Library, and CINAHL were searched to identify relevant studies. Data on treatment completion rates and adverse events were extracted and analyzed descriptively. Results Ten studies involving children and adolescents aged 0–20 years were reviewed. Treatment completion rates were higher with 3HP regimen ranged from 70.9 to 100%, with a favorable safety profile. Mild adverse events, including nausea, vomiting, and abdominal pain, were reported, with no serious adverse events or hepatotoxicity observed. Conclusions The 3HP regimen demonstrates high completion rates and safety profile in children and adolescents with LTBI, highlighting its suitability for this population. Expanding its implementation in programmatic settings is crucial to advancing global TB elimination.